Enabling the transition to a fossil-free steel sector: The conditions for technology transfer for hydrogen-based steelmaking in Europe. (February 2022) - Öhman, Amanda; Karakaya, Emrah; Urban, Frauke
Highlights: Green hydrogen technology can reduce the CO2 from steel-making to nearly zero. Steel based on direct reduction with green H2 is being produced in Sweden. Requires reliance on zero carbon electricity generation. This study explores the conditions for technology transfer from Sweden to EU. This paper outlines the opportunities, barriers and policy recommendations. Abstract: Deep decarbonisation of energy-intensive industries, such as steel production, will be required to achieve the European Union's climate targets. Green hydrogen technology has the potential to reduce the carbon dioxide emissions from iron and steelmaking to nearly zero and mitigate climate change from the industrial sector. The paper is based on an ongoing case in Sweden, where the established firms SSAB, LKAB, and Vattenfall are operating the HYBRIT joint venture. This paper aims to explore the conditions for transferring this technology from Sweden to three primary steel producing countries in Europe: Germany, France and Italy. As a theoretical point of departure, we integrate some concepts from the multi-level perspective and technology transfer theories to better understand transition pathways for hydrogen-based steel production in Europe. We use a case study methodology, including the analysis of more than 20 qualitative interviews and secondary data. The findings of the study conclude that the Swedish iron and steel industry is unique in many ways, yet other European countries are rapidly catching up in hydrogen-based steel production, particularly Germany. Sweden however remains unique in its nearly zero carbon electricity generation and low-cost electricity prices, which can enable green hydrogen production throughout the country. In order to overcome the barriers and create an enabling environment for hydrogen-based steel production, it is key that energy and industry transitions are aligned, that a policy framework that supports these transitions is in place, and that key actors representing all aspects of these transitions cooperate, from industry and research, to academia, policymakers, and civil society.